Perbandingan Perspektif Remaja Pengguna Aplikasi Strava dan Pelari Konvensional di Kabupaten Sumedang dalam Meningkatkan Motivasi Berlari - Widanuzidan; Rizal Ahmad Fauzi; Adang Sudrazat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to compare the perspectives of adolescent Strava users and conventional runners on improving running motivation in Sumedang Regency. A qualitative phenomenological approach was employed involving 20 participants aged 15–21 years, consisting of 10 Strava users and 10 conventional runners selected through purposive sampling. Data were collected through in-depth interviews and Focus Group Discussions (FGDs) and analyzed using thematic analysis with source and method triangulation to ensure data credibility. The findings revealed that Strava users were motivated by digital features, including activity tracking, performance monitoring, challenges, leaderboards, and kudos, which supported self-evaluation, training consistency, and interaction within online communities. In contrast, conventional runners developed motivation through direct running experiences, perceived physical and psychological benefits, habitual exercise, and social support from friends and running communities. Although the two groups demonstrated different sources of motivation, both showed a strong commitment to maintaining running as part of a healthy lifestyle. The study concludes that adolescents' running motivation is influenced by personal experiences, individual needs, the use of digital technology, and supportive social environments that encourage sustained physical activity Keywords: Digital Sports, Running Motivation, Conventional Runners, Teens, Strava